Clinical practice evaluation of opioids induced constipation management in patients with cancer: The EIO-50 project - Vicente Guillem; Francisco Javier Salvador Bofill; Margarita Feyjoo; Antonio Antón; Enrique Aranda; Carlos Camps; Alfredo Carrato; Manuel Constenla; Juan Jesús Cruz-Hernández; Eduardo Díaz-Rubio; Jesús García-Foncillas; Pere Gascón; et al. (Open Journal of Pain Medicine - Peertechz Publications, 2019)
Introduction: Opioid-Induced Constipation (OIC) is a common distressing symptom associated with cancer pain treatment. Consensus guidelines for management of OIC are limited and little is known about the decision making of Health Care Professionals (HCP) for the management of OIC. The aim of this study was to learn about the diagnostic and treatment criteria of OIC management in clinical practice in patients with cancer. Methods: A survey was designed with 50 OIC specific questions and was completed by 135 HCP: 122 medical oncologists (90.4%) and 13 palliative care specialists (9.6%). Result: OIC was considered a relevant side effect by 97% of the specialists. HCP declared differences in the characteristics of OIC depending on whether the patients were treated with major or minor opioids: the percentage of patients developing OIC (54.5% vs 29.8%), OIC intensity (severe in 17% vs 10.8%) and the time to symptoms onset in 1-4 weeks (92.6% vs 73.3%). Only 14% HCP used algorithms for the diagnosis or treatment of OIC. Healthy life-style was considered first-line treatment for OIC by 85.2%. Laxatives were prescribed by 99.3% of HCP, but 32.6% of patients did not achieve a response. Peripherally Active µ-Opioid Receptor Antagonists (PAMORAs) were considered the most effective specific treatment of OIC. Naloxegol was the PAMORA most often used for the treatment of OIC in patients with cancer. Conclusion: The narrow effectiveness of traditional therapies and the emergence of more effective pharmacological approaches suggest the need for standardized and updated guidelines for OIC diagnosis and management in patients with cancer.